IFN-γ-Primed hUCMSCs Significantly Reduced Inflammation via the Foxp3/ROR-γt/STAT3 Signaling Pathway in an Animal Model of Multiple Sclerosis - Ling, Xiao; Wang, Teng; Han, Chao; Wang, Pin; Liu, Xiaoli; Zheng, Chengyun; Bi, Jianzhong; Zhou, Xiaoyan (Frontiers in Immunology, 2022)
Our previous study showed that interferon gamma (IFN-γ) might enhance the immunosuppressive properties of mesenchymal stem cells (MSCs) by upregulating the expression of indoleamine 2,3-dioxygenease. Therefore, we treated experimental autoimmune encephalomyelitis (EAE) mice, an animal model of multiple sclerosis (MS), with IFN-γ-primed human umbilical cord MSCs (IFN-γ-hUCMSCs). This study aimed to investigate the potential therapeutic effects of IFN-γ-hUCMSCs transplantation and to identify the biological pathways involved in EAE mice. Firstly, the body weights and clinical scores of EAE mice were recorded before and after treatment. Then, the inflammatory cytokine levels in splenic cell supernatants were quantified by enzyme-linked immunosorbent assay. Finally, the mRNA expression levels of signal transducer and activator of transduction 3 (STAT3), retinoic acid-related orphan receptor gamma t (ROR-γt), and forkhead box P3 (Foxp3) were detected by quantitative reverse transcription polymerase chain reaction. We observed that IFN-γ-hUCMSCs transplantation significantly alleviated body weight loss and decreased the clinical scores of mice. Additionally, IFN-γ-hUCMSCs transplantation could regulate the production of inflammatory cytokines, interleukin (IL)-10 and IL-17, thereby showing more potent treatment efficacy than human umbilical cord MSCs (hUCMSCs) transplantation (p < 0.05). Compared with the EAE group, the expressions of STAT3 and ROR-γt in the transplantation groups were significantly decreased, but the expression of Foxp3 was significantly upregulated in the IFN-γ-hUCMSCs transplantation group compared to that in the hUCMSCs transplantation group. We assumed that IFN-γ-hUCMSCs may affect the balance of T helper 17 (Th17) cells/regulatory T cells (Tregs) through the Foxp3/ROR-γt/STAT3 signaling pathway to reduce the inflammatory response, thereby improving the clinical symptoms of EAE mice. Our study demonstrated that transplantation of IFN-γ-hUCMSCs could reduce inflammation in EAE mice via the Foxp3/ROR-γt/STAT3 signaling pathway, highlighting the therapeutic effects of IFN-γ-hUCMSCs in patients with MS.